2012
DOI: 10.1021/jm3008486
|View full text |Cite
|
Sign up to set email alerts
|

Development of Oseltamivir Phosphonate Congeners as Anti-influenza Agents

Abstract: Oseltamivir phosphonic acid (tamiphosphor, 3a), its monoethyl ester (3c), guanidino-tamiphosphor (4a) and its monoethyl ester (4c) are potent inhibitors of influenza neuraminidases. They inhibit the replication of influenza viruses, including the oseltamivir-resistant H275Y strain, at low nM to pM levels, and significantly protect mice from infection with lethal doses of influenza viruses when orally administered with 1 mg/kg or higher doses. These compounds are stable in simulated gastric fluid, liver microso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…In addition to the strong hydrogen-bond interactions with the polar amino acid residues, the NA inhibitor also establishes hydrophobic contacts with the conserved residues in the viral NA active sites. Typically, Tamiflu-resistant pH1N1 viruses feature a histidine (His)-to-tyrosine (Tyr) substitution at position 275 of the NA protein, i.e., a His275Tyr (H275Y) NA mutation (N1 numbering) 60 62 . With the H275Y NA mutation, a conformational change occurs at the NA inhibitor binding site, resulting in inhibition of oseltamivir binding and conferring the highest level of resistance to oseltamivir.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the strong hydrogen-bond interactions with the polar amino acid residues, the NA inhibitor also establishes hydrophobic contacts with the conserved residues in the viral NA active sites. Typically, Tamiflu-resistant pH1N1 viruses feature a histidine (His)-to-tyrosine (Tyr) substitution at position 275 of the NA protein, i.e., a His275Tyr (H275Y) NA mutation (N1 numbering) 60 62 . With the H275Y NA mutation, a conformational change occurs at the NA inhibitor binding site, resulting in inhibition of oseltamivir binding and conferring the highest level of resistance to oseltamivir.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested treatment usage of laninamivir (Japan) is beneficial when patients confer resistance to oseltamivir (94,106,107). The recent progress in researching NA inhibitors has mainly focused on the structure modification/optimization of Zanamivir and Oseltamivir, both of which are similar to the Neu analogues (compounds 4-9, Figure 8) (108)(109)(110)(111)(112)(113)(114)(115).…”
Section: Na Inhibitors (Nais)mentioning
confidence: 99%
“…future science group From neuraminidase inhibitors to conjugates: a step towards better anti-influenza drugs? Review In a related study [62,63], Fang and co-workers also explored an OC phosphonate congener, tamiphosphor (20). They found that tamiphosphor and its monoethyl ester (21) were active in preventing human 293T and canine MDCK cells from infection by avian and human influenza viruses, including the OS-resistant strain.…”
Section: Modification Of Za At C-1mentioning
confidence: 99%
“…[108] As tamiphosphor monoethyl ester (21) is shown to possess potent NA inhibitory activity [62,63], the phospha-OS derivatives 44 and 45 (Figure 12) with galactoside linked to the phosphonate group were also synthesized by Streicher and coworkers [109,110]. Compounds 44 and 45 were considered the mimetics of the α2,3and α2,6-sialogalactoside substrates of influenza NA.…”
Section: Derivatives Of Osmentioning
confidence: 99%